Gastrointestinal symptoms in patients with asthma. Issue 2 (1st February 2000) - Caffarelli, Carlo; Deriu, Franca Maria; Terzi, Vittorio; Perrone, Francesca; Angelis, Gianluigi dè; Atherton, David J
Abstract : AIMS: Minor gastrointestinal abnormalities have been reported in children with asthma, but the prevalence of gastrointestinal symptoms in these children has not been studied. METHODS: 75 children with bronchial asthma and an age and sex matched control group were recruited. Parents completed a questionnaire on gastrointestinal symptoms and on asthma. Weight and height were measured; a clinical evaluation of asthma was undertaken and skin prick tests were performed. RESULTS: Children with asthma had a significantly greater frequency of gastrointestinal symptoms, particularly diarrhoea, vomiting, and abdominal pain, than did controls. Gastrointestinal symptoms were slightly more common in children with atopic symptoms other than asthma, or with positive skin prick tests to foods. There was no association between current gastrointestinal symptoms and medications or attacks of asthma. CONCLUSIONS: The occurrence of gastrointestinal symptoms appears to be common in children with asthma. These symptoms might be caused by an atopic gastroenteropathy, which might play a part in the pathogenesis of asthma in some cases.